Effectiveness of the educational program “My friend and I, united against TB” in the prevention of tuberculosis to students of a public educational institution, Ate-Vitarte, Lima - Yanela Ricalde Castillo (2019)
Objective: To determine the effectiveness of the educational program “My friend and I, united againstTB” in the knowledge and attitudes for the prevention of tuberculosis in the second grade students of apublic educational institution in Ate-Vitarte. Materials and methods: the work was quantitative, quasiexperimentaldesign and longitudinal cut, the sample consisted of 102 students from 12 to 15 years,51 of the control group and 51 of the experimental group. The instrument used was the questionnaire,in addition to the creation of the program module that consisted of 9 units addressed in 24 educationalsessions, with a duration of 5 months. Results: the program was effective in knowledge and attitudesabout the prevention of TB with a p-value <0.05. Conclussion: the educational intervention waseffective for the prevention of said disease.